Pengaruh Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian Minuman Bubble Tea Chatime : Studi Kasus pada Pengunjung Mall Suzuya Marelan Plaza Medan - Natasha Jessica; Enda Yunita Surbakti; Erwinsyah Simanungkalit; Irwan Musriza Harahap; Suri Purnami (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to examine in greater depth the influence of brand image and product quality on the purchase decisions of Chatime bubble tea consumers, using a case study of visitors at Mall Suzuya Marelan Plaza Medan. Employing a quantitative research design, the study utilizes a survey method by distributing structured questionnaires to 96 respondents selected through random sampling. The independent variables of the study consist of brand image and product quality, while the dependent variable is purchase decision. Data were analyzed using multiple linear regression with the aid of SPSS version 26 to identify both partial and simultaneous effects. The findings reveal that, when tested partially, brand image shows a negative and non-significant effect on purchase decisions, suggesting that the image of the brand alone does not strongly determine consumer choices. In contrast, product quality demonstrates a positive and significant influence on purchase decisions, indicating that consumers prioritize the quality of the beverage when making purchasing choices. Furthermore, when analyzed simultaneously, both brand image and product quality together exert a significant impact on purchase decisions. The coefficient of determination (R²) of 82.1% signifies that the two independent variables explain a large proportion of the variance, while the remaining percentage is attributed to other factors such as price and promotion.